1995
DOI: 10.1002/gcc.2870130311
|View full text |Cite
|
Sign up to set email alerts
|

Predominant occurrence of somatic mutations of the NF2 gene in meningiomas and schwannomas

Abstract: The NF2 gene is a putative tumor-suppressor gene that, when it is altered in the germline, causes neurofibromatosis type 2, a tumor-susceptibility disease that mainly predisposes to schwannomas and meningiomas. The recent isolation of the NF2 gene on chromosome 22 allows the identification of somatic mutations in human tumors. We have searched for mutations of the NF2 gene in 331 primary human tumors using a screening method based on denaturing gradient gel electrophoresis, which allows the detection of mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 25 publications
2
59
1
3
Order By: Relevance
“…The proposed domains in merlin that mediate these interactions are depicted. Protein 4.1 growth suppression meningiomas and schwannomas; merlin expression is lost in 60% of sporadic meningiomas and 80% of sporadic schwannomas (Bianchi et al, 1994;Ruttledge et al, 1994;Twist et al, 1994;Merel et al, 1995;Gutmann et al, 1997). In addition, re-expression of wild-type merlin in NF2-deficient schwannoma and meningioma cell lines in vitro results in growth suppression (Sherman et al, 1997;Ikeda et al, 1999), and mice with a targeted mutation in the Nf2 gene (Nf2 +/-mice) are prone to the development of malignant and metastatic tumors .…”
Section: Merlin In Tumorigenesis and Developmentmentioning
confidence: 99%
“…The proposed domains in merlin that mediate these interactions are depicted. Protein 4.1 growth suppression meningiomas and schwannomas; merlin expression is lost in 60% of sporadic meningiomas and 80% of sporadic schwannomas (Bianchi et al, 1994;Ruttledge et al, 1994;Twist et al, 1994;Merel et al, 1995;Gutmann et al, 1997). In addition, re-expression of wild-type merlin in NF2-deficient schwannoma and meningioma cell lines in vitro results in growth suppression (Sherman et al, 1997;Ikeda et al, 1999), and mice with a targeted mutation in the Nf2 gene (Nf2 +/-mice) are prone to the development of malignant and metastatic tumors .…”
Section: Merlin In Tumorigenesis and Developmentmentioning
confidence: 99%
“…These neoplasms are usually sporadic, but a few families have been described with multiple tumors inherited in an autosomal dominant fashion (Memon, 1980;Battersby et al, 1986;Butti et al, 1989;Domenicucci et al, 1989), and they also occur in as many as half of the patients with the dominantly inherited familial neuro®bromatosis type 2 syndrome (NF2) (Martuza and Eldridge, 1988). Using positional cloning approaches, the candidate gene for NF2 has been isolated from chromosome 22q12 region (Rouleau et al, 1993;Trofatter et al, 1993), and mutations have been observed in both germ-line of NF2 patients and in about 30% of sporadic meningiomas Lekanne-Deprez et al, 1994;Merel et al, 1995;Papi et al, 1995;De Vitis et al, 1996;Harada et al, 1996). These ®ndings indicate that inactivation of the NF2 gene is important in the development of a signi®cant number of sporadic cases that also generally display LOH for markers located on chromosome 22.…”
Section: Introductionmentioning
confidence: 99%
“…The NF2 gene on human chromosome 22q12 was cloned (36,47), enabling mutational analysis of patient blood samples and "second-hit" analysis of NF2-related tumors. Most NF2 patient tumors and sporadic schwannomas have biallelic inactivating mutations in the NF2 gene (3,8,25,31,37), consistent with its action as a tumor suppressor. Schwannomatosis patients do not carry NF2 germ line mutations, and the molecular basis of their disease remains unknown, yet schwannomas from schwannomatosis patients also have biallelic NF2 mutations (19).…”
mentioning
confidence: 96%